EFFECT OF LOCALLY USED FUNGICIDE MANCOZEB AND INSECTICIDE PROFENOFOS IN RICE FIELDS OF MEGHALAYA ON THE SOIL MICROFLORA - NEHA CHAURASIA (International Journal of Pharma and Bio Sciences, 2014)
Major loss in crop yield and quality are due to biotic stresses known to be a major threat to agriculture. During the past few decades, pesticides have been used frenziedly though, it is not a good measure of sustainable practice. Microalgae easily become the first, in the list of nontarget organisms that are affected by pesticides. The present study provides the first information about the effect of commonly used fungicide mancozeb and insecticide profenofos on growth, pigment, lipid peroxidation, superoxide dismutase, total peroxide, proline and protein content of two important algae Anabaena sp. and Scenedesmus sp. common inhabitants of the paddy fields. Rising concentrations of pesticide accelerated the formation of reactive oxygen species. An increase of 3-4 fold in MDA level at 60ppm of mancozeb and 40 ppm of profenofos reported just after the first day of treatment. Further, a dose dependent increase noticed with the duration of exposure to pesticides. An enhanced superoxide dismutase activity along with peroxide and proline content was also revealed.